Waste of Banana Sticks and Egg Shelves as an Occupational and Safety Health Innovation to Reduce Noise - Alimus, Nur Aqidatul Izzah; Mallapiang, Fatmawaty; Haerana, Bs. Titi; Jusriani, Rini (HIGIENE: Jurnal Kesehatan Lingkungan, 2024)
Noise is unwanted sound and is a source of environmental pollution, especially the work environment. Some of the impacts of noise on health include communication disorders, decreased concentration, and temporary or permanent deafness. One of the alternatives in reducing noise is the use of waste banana stems and egg racks. The purpose of this study was to determine the effectivity of banana stems and egg racks as noise silencer. This type of research is a pure experimental research using a pretest and posttest design with a control group. Noise simulation of 93 dB was given to the control group and the treatment (intervention) group. Furthermore, the intervention group was given banana stem and egg rack noise dampening materials with a composition of 50%: 50%, thickness of 3 cm and 5 cm, and was not given any treatment to the control group. Results showed that the noise dampening material from banana stem fronds and egg racks with a composition of 50% : 50% with a thickness of 3 cm and 5 cm was able to reduce noise. The thicker the material, the greater the intensity of the muted noise. Conclusion: Banana stem waste and egg racks effective as noise silencer. Keywords: waste, banana stem fronds, egg racks, noise, OHS